Chronic treatment with prebiotics, probiotics and synbiotics attenuated cardiac dysfunction by improving cardiac mitochondrial dysfunction in male obese insulin-resistant rats - Wannipa Tunapong (2018)
© 2017 Springer-Verlag GmbH Germany Purpose: In metabolic syndrome, the composition of gut microbiota has been disrupted, and is associated with left ventricular (LV) dysfunction. Several types of prebiotics, probiotics, and synbiotics have been shown to exert cardioprotection by restoring gut microbiota from dysbiosis and reducing systemic inflammation. However, the effects of prebiotics such as xylooligosaccharides (XOS); probiotics such as Lactobacillus paracasei STII01 HP4, and synbiotics on metabolic and LV function in obese insulin-resistant rats have not been investigated. In this study, we hypothesized that prebiotics and probiotics improve metabolic parameters, heart rate variability (HRV), blood pressure (BP), and LV function by attenuating cardiac mitochondrial dysfunction, systemic inflammation, and oxidative stress, and that synbiotics provide greater efficacy than a single regimen in obese insulin resistance. Methods: Rats were fed with either normal diet or high-fat diet (HFD) for 12 weeks and then rats in each dietary group were randomly subdivided into four subgroups to receive either a vehicle, prebiotics, probiotics, or synbiotics for another 12 weeks. Metabolic parameters, BP, HRV, LV function, cardiac mitochondrial function, systemic inflammation, and oxidative stress were determined. Results: HFD-fed rats had obese insulin resistance with markedly increased systemic inflammatory marker [Serum LPS; ND; 0.6 ± 0.1 EU/ml vs. HFD; 5.7 ± 1.2 EU/ml (p < 0.05)], depressed HRV, and increased BP and LV dysfunction [%ejection fraction; ND; 93 ± 2% vs. HFD; 83 ± 2% (p < 0.05)]. Prebiotics, probiotics, and synbiotics attenuated insulin resistance by improving insulin sensitivity and lipid profiles. All interventions also improved HRV, BP, LV function [%ejection fraction; HFV; 81 ± 2% vs. HFPE; 93 ± 3%, HFPO; 92 ± 1%, HFC; 92 ± 2% (p < 0.05)] by attenuating mitochondrial dysfunction, oxidative stress, and systemic inflammation in obese insulin-resistant rats. Conclusion: Prebiotics, probiotics, and synbiotics shared similar efficacy in reducing insulin resistance and LV dysfunction in obese insulin-resistant rats.